Submesoscale variability in a mesoscale front captured by a glider mission in the Gulf of Finland, Baltic Sea - Salm, Kai; Liblik, Taavi; Lips, Urmas (Frontiers in Marine Science, 2023)
Modern research methods enable unfolding the structure of the water column with higher resolution than ever, revealing the importance of submesoscale. Submesoscale processes have intermediate space and time scales of <5 km and a few days in the Baltic Sea. A glider mission was conducted in the Gulf of Finland in May 2018. The appearance of a mesoscale front as a response to the persisting NE–E winds was observed. Within the front, smaller scale features at a lateral scale of a km were apparent. The tracer patterns indicated the presence of two adjacent motions – cold (warm) water penetrating upward (downward) on the lighter (denser) side of the front. We suggest they were traces of ageostrophic secondary circulation emerging while the loss of the upwelling-favorable forcing arrested the strengthening of the front. The analysis showed favorable conditions for the baroclinic and wind-driven instability. Such circulations could work to equalize the differences in cross-front direction, affecting the stratification and acting against the persistence of the mesoscale front. The spatial spectra of isopycnal tracer variance revealed the depth-dependence of the spectral slopes at the lateral scales of 1–10 km in the upper part of the water column. The differing of the slopes in the density layers associated with the mesoscale front indicates that frontal dynamics contribute to the energy cascade.